Singapore Mediation Handbook - ALEXANDER, Nadja (Institutional Knowledge at Singapore Management University, 2019)
The Singapore Mediation Handbook brings together the principles, process and practice of mediation in a single user-friendly volume. Written in an accessible style with anecdotes introducing the themes of each chapter, the book situates mediation in the context of a range of appropriate dispute resolution mechanisms and explores mediation in terms of its values and objectives. Topics explored in the Handbook include: • Cultural and historical perspectives on mediation • Mediation meta model comprising six different mediation practice models • Preparing for mediation • Mediation process and skills • Mediation advocacy • Mediation practice in Singapore • Mediation law • Online dispute resolution The Handbook contains numerous illustrations from Singapore and elsewhere. It also includes up-to-date treatment of the Mediation Act 2017 and the Singapore Convention on Mediation 2018. Singapore Mediation Handbook is a must read for lawyers, judges, academics, students, mediators and other neutrals and anyone wanting to gain an up-to-date and comprehensive understanding of mediation, especially from a Singapore perspective.